Keeping employees accountable for results : quick tips for busy managers - Miller, Brian Cole, 1956- (AMACOM, 2006)
How can busy managers hold employees accountable for results they did or did not achieve? "Keeping Employees Accountable for Results" moves beyond the far-from-ideal annual performance review - which only evaluates what has already occurred, and not what the manager wants to achieve - and shows readers how to effectively manage performance on an ongoing basis. Packed with easy-to-use tools, the book gives time-pressed managers everything they need to ensure results